Difficulties in Cataract Surgery - Zilfyan, Artashes (IntechOpen, 2018)
For thousands of years, cataract surgery continues to be the "pearl" of ophthalmic surgery. It is explained by the fact that cataract removal always leads to an increase in visual acuity of patients. A new technology of cataract removal, phacoemulsification, was introduced by Charles Kelman in 1967. Despite this, it was difficult for the surgeons to transform from extracapsular cataract extraction to the new method - phacoemulsification. Recently, in the ophthalmological practice, the method of femtolaser cataract surgery (FLACS) has been introduced. This method allows you to automatically perform the basic stages of cataract surgery - corneal incisions, capsulorhexis, nucleus fracture. At the same time, to apply the various techniques of cataract surgery, the surgeon must possess virtually all the necessary techniques. This is dictated by the fact that, as a rule, cataract itself is rarely isolated - senile. Knowledge of the basic rules of cataract surgery, the use of pupillary rings and iris retractors in narrow pupils, the use of capsular rings in subluxations of the lens, the use of special modes of phaco in severe late cataracts, and a comprehensive clinical way of thinking can undoubtedly reduce the complications of cataract surgery.